Small inhibitory RNA –– a tool for credentialing candidate genes. (April 2005) - Walgren, Richard A; McLeod, Howard L
The effect of a drug is related to the interaction of the numerous gene products that participate in a drug pathway. The clinical importance of genetic variability on the overall outcome of most drug pathways remains to be determined. As a result, there is a need to efficiently identify the genes that not only participate in the pathway but also play a significant role in regulating the effects of a drug. The emerging technique of specific gene silencing through RNA interference initiated by small inhibitory RNA may prove to be a useful and powerful tool in the credentialing of candidate genes in drug pathways.